(3hhQO (B2003s word 2003 for dummies - (3Lhcjf , OGf (B.s; (3OGf Lhcjf(B.s ((3GdbGgQI (B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B.,s, 2004)
(3jecfc ef EfTGA h JfSjb h WHGYI h JhRjY GdeSJfOGJ(B.s
(3GdJYQa Ydi HQfGeL GdhhQO(B.s
Keywords: (3GdceHjhJQ (B- (3HQGeL(B.s